Cultivation ofÂ straw mushroom (Volvariella volvacea) onÂ oil palm empty fruit bunch growth medium - Sugeng Triyono; Agus Haryanto; Mareli Telaumbanua; Jamalam Lumbanraja; Filip To (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The research aimed to study the effects of size reduction and composting duration of empty fruit bunches (EFB) on straw mushroom production, and to examine the doses of fertilizers commonly used among farmers. Methods The experiment was done in two stages. The first stage was for identifying the optimum physical parameters of EFB, and the second stage focused on enhancing the performance of EFB chosen based on the findings of the first experiment. A randomized complete block design with 3Ã3 factorial arrangement in both stages of the study used the same approach. The first stage had three levels of aggregate sizes factor (S) and three levels of composting duration factor (C) of EFB. The second stage had three levels of NPK factor (N) and three levels of organic fertilizer factor (O). Results Whole stalk EFB had the highest productivity of 2458.47±1015.23 g mâ2. The supplementation of fertilizers increased the EFB decomposition rate and productivity to 2950.24±208.50 g mâ2, and nutritive values (particularly for protein content of 41.00±3.79%). Averaged biological conversion efficiency (BCE) was also improved from 3.61±1.22 to 6.56±0.46%. Conclusions EFB did not need to be cut into smaller pieces, and should not be composted for more than 8 days, because there was a tendency to decrease yield. Supplemental fertilizers increased the decomposition rates of EFB as well as the yield and nutritive values of straw mushroom. BCE can potentially be improved by increasing the dosages of fertilizers.